PRACTICAL APPLICATION OF A HIGH VOLTAGE POWER SUPPLY CABLE FASTENING - Lidanyang Tsetsenbat; Solongo Tsetsenbat; Amgalanzul Jargalsaikhan; Baatarkhuu Dorjsuren (World Science, 2023)
High flame retardant drag chain power sheathed cables are used for equipment power supply, and in the outdoor environment, the power transmission power cable needs to be fixed to the wall, usually along the industrial route. The cable bridge moves, extends more frequently, the power supply cable needs to be fixed with a cable sling device, because there is no such special sling device on the market, so the use of the existing card fixing method leads to the cable often squeezed and damaged insulation layer cable failure power outage. This article addresses this problem and proposes for feasible countermeasures.